Exploring COVID-19 Vaccine Hesitancy Among Stakeholders in African American and Latinx Communities in the Deep South Through the Lens of the Health Belief Model. Issue 2 (February 2022) - Bateman, Lori B.; Hall, Allyson G.; Anderson, William A.; Cherrington, Andrea L.; Helova, Anna; Judd, Suzanne; Kimberly, Robert; Oates, Gabriela R.; Osborne, Tiffany; Ott, Corilyn; Ryan, Melissa; Strong, Christian; et al.
Purpose: The purpose of this study was to qualitatively explore perceptions related to COVID-19 vaccination intention among African American and Latinx participants and suggest intervention strategies. Approach: Ninety minute virtual focus groups (N = 8), segmented by county, race and ethnicity were conducted with stakeholders from 3 vulnerable Alabama counties. Participants: Participants (N = 67) were primarily African American and Latinx, at least 19 years, and residents or stakeholders in Jefferson, Mobile, and Dallas counties. Setting: Focus groups took place virtually over Zoom. Methods: The semi-structured guide explored perceptions of COVID-19, with an emphasis on barriers and facilitators to vaccine uptake. Focus groups lasted approximately 90 minutes and were audio recorded, transcribed, and analyzed by a team of 3 investigators, according to the guidelines of Thematic Analysis using NVivo 12. To provide guidance in the development of interventions to decrease vaccine hesitancy, we examined how themes fit with the constructs of the Health Belief Model. Results: We found that primary themes driving COVID-19 vaccine hesitancy, ordered from most to least discussed, are mistrust, fear, and lack of information. Additionally, interventions to decrease vaccine hesitancy should be multi-modal, community engaged, and provide consistent, comprehensive messages delivered by trusted sources.